AL-QUR’AN DAN MODERASI BERAGAMA PERSPEKTIF AHMAD NURCHOLISH TENTANG PERNIKAHAN BEDA AGAMA - M. Imam Syafi’i; Samsul Ariyadi; Ade Naelul Huda (MISYKAT Jurnal Ilmu-ilmu Al-Quran Hadist Syari ah dan Tarbiyah, 2026)
The interfaith marriage is one of the most controversial issues in religious and legal discourse in Indonesia. Various perspectives have emerged—ranging from strict rejection based on normative religious texts to permissibility on the basis of human rights and religious pluralism, as advocated by Ahmad Nurcholish. In the context of a pluralistic society: Indonesia, religious moderation is a highly suitable approach to avoid falling into extreme ideological positions. This research uses a qualitative methodology with a religious moderation approach. The methods of analysis employed in this thesis include content analysis and comparative analysis. The collected data are critically examined and filtered. As a result that synergy between religion and the state leads to the prohibition of interfaith marriage. This is because it contradicts the primary purpose of marriage in Islam, which is to form a family characterized by sakinah, mawaddah, and rahmah (tranquility, love, and compassion). Interfaith marriage carries a fundamental flaw in terms of religious belief, including the belief system of the Ahl al-Kitāb, which is often used as the basis for its legitimacy. In reality, the majority of Qur’anic exegetes (mufassirīn)—both classical and contemporary—prohibit such marriages.